Improvement of the banana “Musa acuminata” reference sequence using NGS data and semi-automated bioinformatics methods - Martin, G.; Baurens, F.C.; Droc, Gaëtan; Rouard, M.; Cenci, A.; Kilian, Andrzej; Hastie, A.; Doležel, Jaroslav; Aury, J.M.; Alberti, A.; Carreel, F.; D’Hont, Angélique (Springer, 2016)
Recent advances in genomics indicate functional significance of a majority of genome sequences and their long range interactions. As a detailed examination of genome organization and function requires very high quality genome sequence, the objective of this study was to improve reference genome assembly of banana (Musa acuminata).